Improvement of Crop Plants for Industrial End Uses - Ranalli, P. (Springer Netherlands : Imprint: Springer, 2007)
Advanced biotechnologies enable breeders to produce a whole generation of new crops for specialist needs ("designer crops"), including raw materials for the energy, chemical and pharmaceutical industries. This book provides concerns useful to promote an increase of the productivity of crops by using functional genomics (to understand the regulation of plant metabolism at molecular, cellular and whole plants), and the improvement of photosynthetic efficiency (to design new plants with enhanced raw materials percent and recovery). Fundamental thematics have been addressed: metabolic engineering, plant breeding tools, renewable biomass for energy generation, fibres and composites, biopharmaceuticals. The gained know how is relevant to identify bottlenecks in the major production chains and to propose actions for moving these issues forward: in particular to; i) produce new compounds by expressing foreign heterologous genes; ii) modify pathways to influence quality and/or yield of existing indigenous molecules; iii) bioprocess plant or organic waste stream into value-added products. The chapters of this book have been written by experts from all around the world.